Multi-scale friction model for automotive brake system incorporating tribological effects of surface asperities - Jung Yun Won; Hyungjo Seo; Youngjae Kim; Hoejeong Jeong; Joonseok Kyeong; Woojeong Oh; Myoung-Gyu Lee (Materials & Design)
This paper presents a novel multi-scale friction model designed to capture the friction behavior of brake pads by integrating material deformation at different scales. Inspired by previous multi-scale models for the boundary lubrication regime, this model incorporates key features that account for the unique material properties and surface topography of brake pads. A height distribution function derived from surface topology, a contact model representing asperity deformation, and a plowing model addressing the tribological effects of disc asperities form the core framework of the approach. The model primarily focuses on overall material behavior and micromechanical deformation within the brake system while maintaining computational efficiency, providing a mechanics-based, multi-scale representation suitable for large-scale simulations in consideration of pressure, temperature, and topological parameters. To ensure computational efficiency, the model is implemented through a structured approach optimized for finite element (FE) analysis, where it is transformed into an approximate function and embedded in FE subroutines. Its effectiveness is validated through FE simulations of reduced-scale brake dynamometer tests, which demonstrate its predictive capabilities and computational feasibility. The results confirm that the proposed modeling framework accurately predicts the friction coefficient in overall and provides valuable insights into the multi-scale interactions governing friction behavior in brake systems.